Carbon Prices are Redundant in the 2030 EU Climate and Energy Policy Package - Finn Roar Aune; Rolf Golombek (Center for Economic Studies and ifo Institute (CESifo), 2018)
In June 2018, an agreement between key EU institutions – the Commission, the European Parliament, and the European Council – was reached after a long-lasting discourse over the 2030 EU climate and energy policy package. This paper offers a comprehensive assessment of the EU package, with its three main targets: lower greenhouse gas emissions, higher renewable share in final energy consumption, and improved energy efficiency. We find that the renewable and energy-efficiency targets have been set so high that the derived emissions reduction exceeds the EU climate target. Hence, carbon prices are redundant in reaching the EU climate goal. This policy, however, is not cost efficient.
Keywords: Q28; Q41; Q48; Q54; 330; climate policy; renewables; energy efficiency; nuclear phase out; energy modeling